Islamic Education in the Modern Era - Arief Agus Triansyah; Ramadhan Ramadhan (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2025)
Islamic education is a system aimed at shaping individuals with strong faith, mastery of knowledge, and noble character. This article examines three main aspects: its philosophical foundation, objectives, and relevance in the modern era. The philosophical foundation of Islamic education is rooted in the concept of tawhid, which places Allah as the ultimate source of all knowledge. The objectives of Islamic education include strengthening faith, developing moral character, mastering both worldly and spiritual knowledge, and fostering individual independence. In the modern era, Islamic education faces challenges such as globalization, technological advancements, and cultural plurality. However, it also has significant opportunities to thrive through the integration of technology and inclusive approaches. This study provides strategic insights on how Islamic education can remain relevant and contribute to addressing the moral and social challenges of today’s world.